Visual analysis of alpine meadow research trends and hotspots based on VOS viewer - Weishan Lin; Kejia De; Kejia De; Xijie Wei; Xijie Wei; Wei Wang; Wei Wang; Lin Zhang; Lin Zhang; Xuemei Xiang; Xuemei Xiang; Fei Li (Frontiers in Environmental Science, 2023)
In order to reveal the overall research progress in the field of alpine meadows. In this study, a visual clustering analysis of the literature was conducted using VOS viewer software. The English literature related to alpine meadow was searched in the Web of Science database with publication dates limited to 2020–2021, and 3,607 papers were retrieved from the Web of Science using Excel software. By analyzing the basic profiles of annual publication volume, publication country/region, publication journal, publication institution, publication author, and keywords, the hot spots and development trends of alpine meadow research were derived. The data show that China is the top global country for alpine meadow research in the world, the institution with the most publications in Chinese Acad Sci, and the most publications are by Huakun Zhou from China (81 articles); “enzymes”, “climate change” and “microorganisms” are the current hot spots for alpine meadow research. This study analyzes the publication situation, research hotspots and research trends in the field of alpine meadow research to provide a reference for the academic research on alpine meadows for those related to this field.